Urgensi Pancasila Sebagai Dasar Nilai Pengembangan Ilmu, Perlunya Pancasila Sebagai Dasar Nilai Pengembangan Ilmu, Tantangan Pancasila Sebagai Dasar Nilai Pengembangan Ilmu - Ashfiya Nur Atqiya; Ahmad Muhamad Mustain Nasoha; Afila Fitroh Rohmawati; Nabila Marwah Safira; Salma Azzahro Rahayu (International Forum of Researchers and Lecturers, 2024)
As a state ideology, Pancasila encapsulates the religious and cultural principles held by the people of Indonesia. All aspects of national and state society can be accommodated by these values. It is the same with scientific endeavours. If Indonesia is serious about advancing its scientific and technological capabilities, it should look to the five tenets of Pancasila as a roadmap. With any luck, this paper will help spread the word about Pancasila and its importance in guiding Indonesia's scientific community towards better technological practices.